Genetic variability and diversity studies in niger (Guizotia abyssinica L Cass.): Genetic variability and diversity studies in niger (Guizotia abyssinica L Cass.) - P K JAGTAP; C S PATEL; P M MISTRY (Journal of Oilseeds Research, 2020)
A wide range of phenotypic variation was observed for most of the characters studied for genetic variability assessment in niger. Seed yield/plant showed highly significant and positive correlation with number of branches/plant, number of capsules/plant, capsule diameter, number of seeds/capsule, 1000 seed weight, leaf area and harvest index at both genotypic and phenotypic levels, while it was found to be positive and significant correlation at genotypic level with plant height. Among eleven traits studied for diversity, harvest index followed by number of seeds/ capsule, seed yield/plant, days to 50% flowering, number of branches/plant contributed maximum towards the total genetic divergence.